Upaya Penghematan Air Irigasi dan Peningkatan Produksi Padi Sawah Melalui Penerapan Irigasi Terputus-putus (Intermittent Irrigation) - Muhammad Idrus (Jurusan Teknologi Pertanian, 2021)
The research was conducted in rainfed rice field at Cisarua Village, Natar Sub District, Lampung Selatan Region to find out intermittent irrigation methode which efficient in using water and high yield. The experimental design was using completely randomized design (CRD) with four irrigation treatments and replicated thrice. The treatments consist of intermittent irrigation with soil hair-crack indicator (II1), intermittent irrigation with water in the perforated PVC pipe fell 10 cm below ground level (II2), intermittent irrigation with irigation interval 2 days indicator (II3), and control. Preparation of seedling for the intermittent irrigation treatment using nursery plate, but for controll teratment using rice field. The treatment the intermittent irigation were using transplanting of 1 young seedling (10 days after seeding) at wider space 25 cm x 25 cm, and for the control treatment transplanting of 3-5 old seedling (20 days after seeding) at the same space. The research result showed that the highest total amount of water irrigation aplication was happened on intermittent irrigation with 2 days irrigation interval indicator of 717 mm, in the same as with control treatment, but the lowest total amount of water irrigation application was happened in the intermittent irrigation with soil hair-crack indicator of 460 mm or only amount 64,16% of control treatment. In this case showed that intermittent irrigation with soil crack-hair indicator can save amout of water irrigation application of 35,84%. Grain yield of rice on the treatment of intermittent irrigation with soil hair-crack indicator and irrigation interval 2 days indicator not significantly different but signifcantly different and higher compare to intermittent irrigation with water level in the perporated PVC pipe fell 10 cm below ground level and the control trentmen. The average grain yield of rice on intermittent irrigation with soil hair-crack indicator 8,783 kg/ha with highest irrigation water productivity of 1,91 kg/m3, but on the control treatment only 6,528,08 kg/ha with lowest irrigation water productivity of 0,91 kg/m3.